Dual-responsive ultrathin 1T-phase niobium telluride nanosheet-based delivery systems for enhanced chemo-photothermal therapy. Issue 38 (8th September 2021) - Liu, Hao; Chen, Haolin; Liu, Xiaoying; Mo, Luoqi; Chen, Chao; Guo, Zhouyi; Liu, Zhiming
Abstract : 1T-phase niobium telluride (NbTe2 ) nanosheets are becoming increasingly important in emerging fields, such as spintronics, sensors and magneto-optoelectronics, due to their excellent physical and chemical properties. Abstract : 1T-phase niobium telluride (NbTe2 ) nanosheets are becoming increasingly important in emerging fields, such as spintronics, sensors and magneto-optoelectronics, due to their excellent physical and chemical properties. However, exploration on their biomedical applications are limited. Herein, ultrathin 1T-phase NbTe2 single-crystalline nanosheets with excellent photothermal performance, high drug-loading rate, near-infrared (NIR) light/acidic pH-triggered drug release, and low toxicity were developed for potentiated photothermal therapy. Importantly, they showed excellent biocompatibility in vivo and in vitro . NbTe2 nanosheets loaded with integrated stress response inhibitors (ISRIB) could achieve chemo-photothermal therapy of tumors through the ATF4–ASNS signaling axis. Ultrathin 1T-phase NbTe2 single-crystalline nanosheets with unique photothermal properties, drug loading rate and safety provide dramatic possibilities in biomedical applications, such as tissue imaging, photothermal therapeutics and pharmaceutics.